2003
DOI: 10.1177/0145482x0309701107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mobility Training on Gait and Balance

Abstract: Approximately 3.8 million persons over age 65 are visually impaired (that is, are blind or have low vision), of whom about 173,000 are legally blind veterans (Department of Veterans Affairs, 2003). The population of legally blind veterans is projected to increase to nearly 1 million by 2010 (Veterans Benefits Administration, 2001). As these demographic changes occur, it is important to gain a better understanding of the effects of orientation and mobility (O&M) training on older people with visual impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…With the inertial sensors and the presented metrics, it will be possible to obtain outcome measures as stride rate, gate velocity (meters per minute), and grip characteristics. Additionally, the provided coverage and long mechanics will allow interpretations of the sweeping characteristics as amplitude, frequency and the ability to detect obstacles in the path, as it has been done previously either with more complex acquisition systems [ 15 , 50 , 51 ], simulated [ 52 ] or in some cases manually [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the inertial sensors and the presented metrics, it will be possible to obtain outcome measures as stride rate, gate velocity (meters per minute), and grip characteristics. Additionally, the provided coverage and long mechanics will allow interpretations of the sweeping characteristics as amplitude, frequency and the ability to detect obstacles in the path, as it has been done previously either with more complex acquisition systems [ 15 , 50 , 51 ], simulated [ 52 ] or in some cases manually [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several references [ 6 , 8 , 9 , 10 , 11 , 12 ] the emphasis and importance of the O&M service and training in order to improve the quality of life, is widely emphasized [ 5 , 13 ]. Therefore, there is a specific health discipline in charge of the study, development, and improvement of the O&M training in VIP [ 14 , 15 , 16 ]. The latest report of the international approaches to rehabilitation programs from the World Blind Union [ 7 ] presents two important challenges on which this project was motivated: (1) the limitation of resources to provide basic rehabilitation services and (2) transportation and geographic limitations, where many VIP must displace themselves to other cities in order to access the rehabilitation services which, in some cases, is impossible for some VIP.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical observations and research data on RP report that subjects travel in familiar and less complex environments to reduce sustained effort, decrease walking speed and have difficulty executing a second task [2]. They manifest slower reaction time [3] and avoid night time travel [4]. They often travel without mobility aid, even when their vision is not functional enough to walk without a tool; this behaviour can modify posture [5].…”
Section: Introductionmentioning
confidence: 99%
“…9 Few studies have been published that assess the effects of training on balance skills in individuals with visual impairment. Using the Berg Balance Scale prior to and after orientation and mobility training, negligible effects have been shown 22 and gait speed remained unaffected. 22,23 A pilot study reported that the length of time of the one-leg stance increased after Tai Chi and orientation and mobility training, 24 but no recommendation could be proposed.…”
mentioning
confidence: 99%